MISUNDERSTANDING OF THE QUR’AN VERSES AMAR MA’RUF NAHI MUNKAR BY EXTREME MUSLIM IN INDONESIA - Azisi, Ali Mursyid; Ilmiyah, Dina Faiqotul; Ningrum, Velida Apria; Salamullah, Muchammad Amiruddin; Majid, Abdul (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2023)
This article examines how the misunderstanding of the implementation of the Qur'anic text amar ma'ruf nahi munkar by extreme Islamic groups (HTI, Salafi-Wahabi, and FPI), especially in Indonesia. Presenting the phenomenon that often occurs and the response to acts of violence accompanied by the destruction of facilities is a form of implementing verses that are not in line with the nature of Islam, which was revealed as a religion that perfects all things, including morals. This article is written with a qualitative method using library research steps by referring to appropriate, relevant, and accurate references that can later be accounted for. This article aims to find out how mistakes have been made in interpreting the text of amar ma'ruf nahi mungkar by extreme Islamic groups. The findings of this research are that the Qur'anic verse amar ma'ruf nahi munkar fails to be understood by extreme Islamic groups. The verse upholds goodness and prevents evil instead of being applied with violence. The meaning contained in word